2021
DOI: 10.1038/s41416-021-01462-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological basis for novel mesothelioma therapies

Abstract: Mesothelioma is an aggressive cancer that is associated with exposure to asbestos. Although asbestos is banned in several countries, including the UK, an epidemic of mesothelioma is predicted to affect middle-income countries during this century owing to their heavy consumption of asbestos. The prognosis for patients with mesothelioma is poor, reflecting a failure of conventional chemotherapy that has ultimately resulted from an inadequate understanding of its biology. However, recent work has revolutionised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 217 publications
(237 reference statements)
0
17
0
Order By: Relevance
“…Although the data reported in this review provide several information about the MPM TME players and its close connections, many questions related to their clinicopathological impact are still opened and a better knowledge of them may help cancer research for developing TME-based therapeutics able to overcome the poor overall survival of MPM patients, the chemoresistance mechanisms and the relapse of the tumor. Although the last therapy targeting TME in mesothelioma clinical trials including the immunotherapy and the combination immuno/chemotherapy are promising therapeutic approaches [ 148 , 149 , 150 ], the efficacy of these strategies remains limited. A wide consideration of TME as the main player of cancer initiation and progression is required, in order to have in-depth knowledge of TME complexity and to design new drugs that target not only tumor cells but also the TME players supporting cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the data reported in this review provide several information about the MPM TME players and its close connections, many questions related to their clinicopathological impact are still opened and a better knowledge of them may help cancer research for developing TME-based therapeutics able to overcome the poor overall survival of MPM patients, the chemoresistance mechanisms and the relapse of the tumor. Although the last therapy targeting TME in mesothelioma clinical trials including the immunotherapy and the combination immuno/chemotherapy are promising therapeutic approaches [ 148 , 149 , 150 ], the efficacy of these strategies remains limited. A wide consideration of TME as the main player of cancer initiation and progression is required, in order to have in-depth knowledge of TME complexity and to design new drugs that target not only tumor cells but also the TME players supporting cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 is generally expressed on the immune cells’ surface and once activated in response to ligand binding, they negatively regulate T cell activation. The anti-PD-1 antibodies, pembrolizumab, nivolumab and durvalumab have shown promising results in clinical trials; however, a heterogenic response among MPM patients was reported [ 147 , 148 ]. To increase the efficacy of these treatment modalities, combinatory strategies are under clinical investigation, with both CTLA-4 and PD-1 inhibitors as well as PD-1 inhibitors plus chemotherapy [ 147 , 149 ].…”
Section: Therapeutic Approach Targeting Tmementioning
confidence: 99%
“…Histologically, PM has been classified into three major subtypes: epithelioid (50–70% of cases), sarcomatoid (10–20% of cases) and biphasic, a combination of epithelioid and sarcomatoid (30% of cases) [ 3 ]. Of note, sarcomatoid mesothelioma has a poor prognosis, with a median survival of 4 months, while epithelioid and biphasic PM have better outcomes, of 13.1 and 8.4 months, respectively [ 1 , 4 ]. The first-line systemic treatment for unresectable PM is the combination of cisplatin and pemetrexed [ 2 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cytotoxic chemotherapy and ICI agents, several new agents were recently designed to treat MPM. Anetumab ravtansine comprises a human anti-mesothelin IgG1 antibody conjugated via a disulfide-containing linker to the maytansinoid tubulin inhibitor DM4, which disrupts microtubule function and inhibits mitosis [ 30 ]. Mesothelin, a glycosylphosphatidylinositol (GPI)-anchored glycoprotein, is a tumor differentiation antigen frequently expressed at high levels in tumors, such as mesothelioma, ovarian, pancreatic, and lung adenocarcinomas, and showing restricted expression in nonmalignant tissues [ 31 ].…”
Section: Discussionmentioning
confidence: 99%